IDENTIFICATION OF MACROALGAE IN THE COASTAL AREA OF BUDO TOURISM VILLAGE, WORI, NORTH MINAHASA - Watung, Fernando; Supit, Annely; Setyawati, Iriani; Kamagi, Decky; Agustina, Tika Puri; Rukmana, Musma; Hasmiati, Hasmiati (Indonesian Biodiversity Journal, 2024)
Algae are lower plants that do not have differentiated structures such as roots, stems, and leaves; although they may appear to have differences, they are actually just thallus forms. Macroalgae have macroscopic body shape and size consisting of fronds without distinct roots, stems, and leaves. Macroalgal diversity is not only reflected in their ecological and economic significance but also in their high species richness and wide geographical distribution within aquatic ecosystems. However, research on the species diversity of macroalgae in Budo Tourism Village Beach, North Minahasa remains limited. This study aims to identify the macroalgal species in the Budo Tourism Village, Wori, North Minahasa area. The research employed the line transect and quadrat-based sampling method, which was implemented at two distinct station locations: Station I (rocky reef substrate) and Station II (sandy-muddy substrate). Macroalgae identification was facilitated by utilizing the comprehensive identification textbooks. The research reveals the presence of four macroalgal species, comprising three brown algae (Phaeophyceae), namely Padina boergesenii, Sargassum llinearifolium, Turbinaria ornata and one red algae (Rhodophyceae), Gracilaria corticata. Sargassum linearifolium, Padina boergesenii, and Gracilaria corticata was found in rocky reef substrate. Turbinaria ornate and Padina boergesenii was found in sandy-muddy substrate.